Descriptions of immatures of the South American plant hopper, Taosa (C.) longula - Marino, Ana Maria (2012)
Descriptions of the immature stages of Taosa (Cuernavaca) longula Remes Lenicov (Hemiptera: Fulgoroidea: Dictyopharidae) and a key for their identification is provided for specimens collected on the water hyacinth, Eichhornia crassipes (Martius) Solms-Laubach (Commelinales: Pontederiaceae), in northeastern Argentina and Peru. Newly emerged nymphs from eggs collected in the field were reared in rearing chambers, and each stage was fixed to microscopic examination and illustration. Fifth nymphal instars can be easily recognized from congeners by the brown marked pattern coloration, shorter vertex, and the distinguishable median carina along the frons. Information on behavior and developmental time is also included.